Critical Aspects of AGC Emerging from Optimal Control to Machine Learning Techniques - Gulshan Sharma; Kabulo Loji (IAES Indonesian Section, 2020)
With the emphasis towards renewable energy lot more advancement has been done in the field of electric energy system and it is expected that future energy system may have wind power dominating control areas or hydro power be it bulk hydro or micro hydro based power generations in order to cater the rising energy demands of the modern society. Hence, automatic generation control (AGC) plays a crucial role in the modern electrical energy system in order to maintain the frequency standards to nominal value besides maintaining the power interchange between the interconnected controls areas in order to distribute value and cost effective power. This paper presents the literature survey related to some of the critical aspects of AGC such as diverse sources power generations, hydro dominating control areas, wind power based power generations and applications of flexible alternating current transmission system (FACTS) in AGC. This paper also discusses the novel control designs based on the concept of optimal control, output vector feedback, model predictive control, robust control and finally the machine learning based AGC designs are explored and the critical gaps among the available research work are well presented and discussed.